2010
DOI: 10.1183/09059180.00005710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic bronchoscopy: state of the art

Abstract: Since the introduction of the flexible fibreoptic bronchoscope in the late 1960s there have been relatively few technological advances for three decades, aside from the development of a white light video bronchoscope with a miniature charge-coupled device built in its tip replacing the fibreoptics. White light flexible videobronchoscopy with its ancillary devices (forceps biopsy, bronchial brushing, bronchoalveolar lavage, bronchial washings and transbronchial needle aspiration) has long been the only establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 42 publications
1
18
0
5
Order By: Relevance
“…Así la decisión de realizar una BTB, en ausencia de un diagnóstico clínico-radiológico de certeza, depende de las característi-cas del paciente (edad, estado funcional) y de la sospecha diagnóstica. El rendimiento diagnóstico de la BTB dependerá de la distribución topográfica y de la especificidad morfoló-gica de la lesión 1,15 . La BTB tiene una alta rentabilidad en el diagnóstico de sarcoidosis, linfangitis carcinomatosa, daño alveolar difuso, algunas infecciones, proteinosis alveolar y neumonía eosinofílica; rentabilidad moderada en algunas vasculitis, amiloidosis, histiocitosis X o LAM y una baja rentabilidad en el diagnóstico de las NII (con excepción de la NOC), la bronquiolitis constrictiva o enfermedad pulmonar veno oclusiva 1,16 .…”
Section: Biopsia Transbronquialunclassified
“…Así la decisión de realizar una BTB, en ausencia de un diagnóstico clínico-radiológico de certeza, depende de las característi-cas del paciente (edad, estado funcional) y de la sospecha diagnóstica. El rendimiento diagnóstico de la BTB dependerá de la distribución topográfica y de la especificidad morfoló-gica de la lesión 1,15 . La BTB tiene una alta rentabilidad en el diagnóstico de sarcoidosis, linfangitis carcinomatosa, daño alveolar difuso, algunas infecciones, proteinosis alveolar y neumonía eosinofílica; rentabilidad moderada en algunas vasculitis, amiloidosis, histiocitosis X o LAM y una baja rentabilidad en el diagnóstico de las NII (con excepción de la NOC), la bronquiolitis constrictiva o enfermedad pulmonar veno oclusiva 1,16 .…”
Section: Biopsia Transbronquialunclassified
“…Although initial reports suggested that cytological samples were inadequate [16], recent findings have shown that minimally invasive techniques might be sufficient [17][18][19], [20•]. Rapid on-site evaluation (ROSE) in the bronchoscopy suite may be instrumental in such cases in order to guarantee that the sample obtained is adequate for both a diagnosis and mutation analysis in the majority of cases.…”
Section: Bronchoscopy and Targeted Therapiesmentioning
confidence: 99%
“…É uma ferramenta diagnóstica inestimável para muitas desordens pulmonares, sendo considerado um procedimento de baixa morbidade (0,1-2,5%) e muito baixa mortalidade (<0,05%) 2,3 . O termo biópsia endobrônquica (BE) ou biópsia brônquica engloba a análise microscópica de lesões endobrônquicas ou da mucosa brônquica.…”
Section: Introductionunclassified